Application of Virtual Reality (VR) Technologies in Management and Education - A. I. Sosnilo (Управленческое консультирование, 2021)
The article analyzes immersive education, augmented and virtual reality technologies and their forms of application in modern economic conditions both abroad and in Russia. Advantages and disadvantages of application of these technologies and constraints of their development are outlined. Reasons and factors inﬂuencing the application of these technologies in manage-ment and education are justiﬁed. We studied the change in interest in the concept of “virtual reality” according to the search queries of the Google trends service. The practice of AR/VR tools application in management and educational process was summarized. Statistics on the prospects for the development of the global market for virtual and augmented reality tech-nologies were analyzed. The domestic practice of development of AR/VR projects and platforms is summarized. Proposals for the development of immersive technologies in education and business are formulated.